Satin Bowerbird optimization algorithm for the Application of Optimal power flow of power system with FACTS devices (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The following research paper, addresses the issue of the optimal power flow ( OPF) of power system dealt by the proposal of  adapting flexible ac transmission FACTS devices with Satin Bowerbird optimization (SBBOA) algorithm.  The SBBOA is bio-inspired algorithm; it is carried out based totally on the principle of ‘female-attracted-by-male’ for breeding. The algorithm that is proposed is tested by usingIEEE-30 bus and IEEE-57 bus test systems with FACT devices of two different types. The following are the two types of FACT devices that are kept at fixed locations:FACT devices that are kept at fixed locations:Thyristor controlled series capacitor andThyristor controlled phase shifterThe objective of the present study aims at four different functions. They are:(a) Minimizing the cost of fuel (b)  Minimizing active power loss during transmission(c) Reduction of emission and(d) Minimizing the combination of economic and environmental cost.The SBBOA give the finest simulation outcomes than lately proposed optimization algorithms given in the literature.